Effects of Ill Health and Morality in the Sick Role Model (JOURNAL OF INNOVATIVE RESEARCH IN MANAGEMENT AND HUMANITIES, 2010)
The paper focuses on ill health and the issue of morality against the backdrop ofthe sick role - a functionalist approach to ill health initiated by Talcott Parsons. Afundamental reality is that being ill, is an unpleasant experience and has disruptive impactson a group or society. What the ill person needs most is not blame but supportiveinteraction with family members and assistance from medical experts for him to get better.But more often than not, rather than gets the support, the gatekeepers of the sick role modelmorally evaluate ill health, thus, making the sick person blameworthy by attributing his/herill health to moral failings and irresponsible lifestyle. The paper argues that moralevaluation of people with ill health or victim blaming ideology invalidates the sick rolemodel. This serve as a legitimization of the denial of the rights and obligations of the sickperson as stipulated by the sick role principle. The implication is that the individual isabandoned at the mercy of illness while its disruptive effect on the group or societyprevails. The paper suggests re socialisation programme for the gatekeeper of the sick roleas a way out of the crisis of moral evaluation of ill health
Keywords: heath, ill health, morality, sick role